Enthesitis in Bowel-Associated Dermatosis-Arthritis Syndrome in an Ulcerative Colitis Patient - Alshahrani, Khalid S.; Almohaya, Abdulellah M.; Hussein, Rayan S.; Ali, Rania H. (Case Reports in Rheumatology, 2022)
Bowel-associated dermatosis-arthritis syndrome (BADAS) is a rare and recurrent neutrophilic dermatosis condition. Due to the rarity of this syndrome and the difficulty of the disease recognition and management, there was no clear reported incidence rate of this syndrome. 20% of patients after ileojejunal bypass surgery for morbid obesity were reported, by Jorizzo et al., to have BADAS. The underlying etiology of BADAS is not fully understood; therefore, the diagnosis of this condition is difficult and the approach for the management as well. Herein, we report a case of BADAS with unusual musculoskeletal presentation.